Comparing target detection errors in visual search and manually-assisted search - Solman, Grayden J. F.; Hickey, Kersondra; Smilek, Daniel (Attention, perception & psychophysics, 2014)
Subjects searched for low- or high-prevalence targets among static nonoverlapping items or items piled in heaps that could be moved using a computer mouse. We replicated the classical prevalence effect both in visual search and when unpacking items from heaps, with more target misses under low prevalence. Moreover, we replicated our previous finding that while unpacking, people often move the target item without noticing (the unpacking error) and determined that these errors also increase under low prevalence. On the basis of a comparison of item movements during the manually-assisted search and eye movements during static visual search, we suggest that low prevalence leads to broadly reduced diligence during search but that the locus of this reduced diligence depends on the nature of the task. In particular, while misses during visual search often arise from a failure to inspect all of the items, misses during manually-assisted search more often result from a failure to adequately inspect individual items. Indeed, during manually-assisted search, over 90 % of target misses occurred despite subjects having moved the target item during search.